Ketidaknyamanan Pemakaian Lensa Progresif Terhadap Penderita Presbiopia Di Barran Optikal Batusangkar - suryanta, Dolly iman (CV. ITTC INDONESIA, 2023)
This scientific paper discusses the Difficulty of Using Progressive Lenses in Presbiopia Patiens in Andalas Optical. This study aims to: (1) find out what are the difficulties experienced by presbyopic patients with progressive lens use at Andalas Optical, and (2) to find out how to handle the difficulties experienced by presbyiopic patient with progressive lens use at Barran Optical. The type of research used is descriptive quantitative. The population in this study were all patients with prebyopia who wore progressive lenses during the study. The sampling in this research is the total sampling technique. Data were collected through questionnaires, then the data were discussed according to the theory proposed in the literature review. The results showed that the respondents showed (67%) difficulty in using progressive lenses and (33%) comfortabel in using progressive lenses in presbyopic patients. From these results, it can be understood that many respondents with prebyopia find it difficult to use progressive lenses and there are some respondents who are comfortabel wearing their glasses with progressive lenses. The results showed that the respondents showed (67%) difficulty in using progressive lenses and (33%) comfortabel in using progressive lenses in presbyopic patients. From these results, it can be understood that many respondents with prebyopia find it difficult to use progressive lenses and there are some respondents who are comfortabel wearing their glasses with progressive lenses. Based on the results of this study, there are several suggestions submitted to respondents so that (1) patients should pay more attention to eye health (2) have their eyes checked once every 6 months or at least 1 time 1 year in order to find out how the development of vision. To Barran Optical RO to choose the rightframe for progressive lens wearers and lenses that match the frame and provide education in the use of progressive lenses.